Implementation Evaluation of Public Participation in Drafting Laws Application as A Realization of Bureaucracy Reform Principles in the House of Representatives of the Republic of Indonesia - Muhamad Arby Hariawan (STIA Bengkulu, 2023)
In order to implement good public service, bureaucracy reform principles are being applied by multitudinous government institutions. The House of Representatives of the Republic of Indonesia with the Center for Drafting Laws as its expert institution in drafting law has constructed an innovation which is called the Public Participation in Drafting Laws application as a realization of the earlier principles. This research was designed to evaluate the implementation of bureaucracy reform values in the Public Participation in Drafting Laws application. Moreover, this research used a qualitative descriptive approach as a way to acquire comprehensive understanding about the application of bureaucracy reform points in the released innovation as a main focus of the research. Researcher used Implementation Evaluation Model Theory by Stake as the grand analysis. In addition, essential data to strengthen this study was collected by doing several methods such as interview, observation, and literature study. The result of this research reports that the principles in the transformation of the bureaucracy ecosystem have been implemented by the House of Representatives in the Public Participation in Drafting Laws application in several occasions such as planning, providing resources, coordinating, and monitoring. However, implementing and evaluating require to be developed as a way to ameliorate this innovation.